Bi‐allelic pathogenic variants in NDUFC2 cause early‐onset Leigh syndrome and stalled biogenesis of complex I. Issue 11 (24th September 2020) - Alahmad, Ahmad; Nasca, Alessia; Heidler, Juliana; Thompson, Kyle; Oláhová, Monika; Legati, Andrea; Lamantea, Eleonora; Meisterknecht, Jana; Spagnolo, Manuela; He, Langping; Alameer, Seham; Hakami, Fahad; et al.
Abstract: Leigh syndrome is a progressive neurodegenerative disorder, most commonly observed in paediatric mitochondrial disease, and is often associated with pathogenic variants in complex I structural subunits or assembly factors resulting in isolated respiratory chain complex I deficiency. Clinical heterogeneity has been reported, but key diagnostic findings are developmental regression, elevated lactate and characteristic neuroimaging abnormalities. Here, we describe three affected children from two unrelated families who presented with Leigh syndrome due to homozygous variants (c.346_*7del and c.173A>T p.His58Leu) in NDUFC2, encoding a complex I subunit. Biochemical and functional investigation of subjects' fibroblasts confirmed a severe defect in complex I activity, subunit expression and assembly. Lentiviral transduction of subjects' fibroblasts with wild‐type NDUFC2 cDNA increased complex I assembly supporting the association of the identified NDUFC2 variants with mitochondrial pathology. Complexome profiling confirmed a loss of NDUFC2 and defective complex I assembly, revealing aberrant assembly intermediates suggestive of stalled biogenesis of the complex I holoenzyme and indicating a crucial role for NDUFC2 in the assembly of the membrane arm of complex I, particularly the ND2 module. Synopsis: This work describes the first confirmed pathogenic variants in NDUFC2 in a case of mitochondrial disease presenting with symptoms of Leigh syndrome and a severe deficiency in OXPHOS complex I. NDUFC2 was shown to be important for the assembly of the membrane arm of complex I. Bi‐allelic variants in NDUFC2 (NM_004549.6) were identified in 2 families by whole exome sequencing. Two affected siblings in one family were homozygous fora c.346_*7del, p.(His116_Arg119delins21) variant and an affected individual from another family was homozygous for a c.173A>T, p.(His58Leu) NDUFC2 variant. Fibroblasts from one case from each family showed decreased protein levels of NDUFC2 and other subunits of OXPHOS complex I. Introduction of wild‐type NDUFC2 into fibroblasts samples from affected individuals by lentiviral transduction ameliorated the complex I defects, confirming pathogenicity of these NDUFC2 variants. Complexome analysis revealed an increase in specific aberrant complex I assembly intermediates consistent with a stalling of complex I assembly, particularly the assembly of the ND2 module. Abstract : This work describes the first confirmed pathogenic variants in NDUFC2 in a case of mitochondrial disease presenting with symptoms of Leigh syndrome and a severe deficiency in OXPHOS complex I. NDUFC2 was shown to be important for the assembly of the membrane arm of complex I.